Electronic Enrichment Book Design “Solar Energy and Its Benefits” to Improve Environmental Problem Solving Skills - Jufiani Ulfa; Desnita (Jurnal Penelitian Pendidikan IPA, 2025)
This study is a development research using the Borg and Gall model. This study aims to determine the design of electronic enrichment books. The instrument used was a questionnaire and the data was analyzed descriptively based on the validity and practicality score sheets. The product was validated by experts and the practicality was validated by teachers and students. The results of the validity data showed an average value of all aspects of0.88 with very high criteria. The validity results show that the electronic enrichment book meets valid data so that it is worthy of use and a little revision and the practicality results show that the electronic enrichment book has an average value of all aspects of 0.81 with very high criteria from teacher practitioners and an average value of all aspects of 0.70 with high criteria from student practitioners. The conclusion obtained is that the design of this electronic enrichment book can be used from the valid results and can make it easier to use electronic enrichment books from the results of practitioners.